What makes a young entrepreneur? - David G. Blanchflower; Andrew J. Oswald (Institute for the Study of Labor (IZA), 2007)
This paper documents some of the patterns in modern microeconomic data on young people's employment, attitudes and entrepreneurial behaviour. Among other sources, the paper uses the Eurobarometer Surveys; the Labour Force Surveys from Canada and the Current Population Survey in the United States. The first conclusion is that self-employed individuals - a special but well-defined entrepreneurial group - report markedly greater well-being than equivalent employees. Their job satisfaction and life-satisfaction are all higher than workers of identical personal characteristics. The second conclusion is that individuals say they would like to be self-employed. There is, according to the survey data, a large pool of potentially entrepreneurial people. Across the West, many millions of employees would apparently prefer to be self-employed. Third, we showed that another important determinant of being self-employed is having a self-employed parent. This appears to help young people to set up in business themselves. It is unclear whether this is done by inheriting the business, or working in the family firm or actually setting up a new business entirely.
Keywords: 330; Youth entrepreneurship; self-employment; Jugendliche Arbeitskräfte; Selbstständige; Unternehmer; Arbeitszufriedenheit; Lebenszufriedenheit; EU-Staaten; Kanada; USA